If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 5) + 4 = 0 Reorder the terms: 2(5 + x) + 4 = 0 (5 * 2 + x * 2) + 4 = 0 (10 + 2x) + 4 = 0 Reorder the terms: 10 + 4 + 2x = 0 Combine like terms: 10 + 4 = 14 14 + 2x = 0 Solving 14 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 2x = 0 + -14 Combine like terms: 14 + -14 = 0 0 + 2x = 0 + -14 2x = 0 + -14 Combine like terms: 0 + -14 = -14 2x = -14 Divide each side by '2'. x = -7 Simplifying x = -7
| 3.8=0.5(8n-46) | | 8a-3=11 | | 5x+3(2x+-8)=9 | | 4(x-(1/2))^2 | | -3x^3+4x^2+x+6=0 | | 4c(3c^3+4)=(3c^3-4) | | 3y+1-36=12(1)+y-9 | | (5a+4b)=(5a-4b) | | (5a+4b)=(4a-4b) | | 5(16)+w-35=7w+16-49 | | 96/y/y=4 | | 4y(y)=96 | | 1x^2-2x-48=0 | | 4-3a=29 | | 9+20x=29x | | cosx+3.8=0 | | 10p-27=7p | | 9 | | x-8+2(3x+3)=-3(x+2) | | 4=x+5x | | 7+3(3y-3)=-2(4y-8)+5y | | -3(5y-1)+3y=6(y+1) | | -2*x^3+17*x^2-40*x+16=0 | | 18+15y-23=y+4(18)+21 | | x^6+13x^5+42x^4=0 | | c+2(19)+3=19+5c-30 | | kx^2-8x+6=0 | | 9(14)+u-40=19u+14 | | 12/9=4/× | | f(x)=x^3-3x^2+4x+1 | | 72/8-3= | | 2[p-(2p+13)+8]=2(p+5) |